PENGARUH PENGELOLAAN KELAS BELAJAR HOMOGEN TERHADAP KONSENTRASI BELAJAR PESERTA DIDIK DI MI DARUL FIKRI PONOROGO - Fitri Rochayati; Syarifan Nurjan; Ayok Aryanto (TARBAWI:Journal on Islamic Education, 2020)
The management of learning classes at MI Darul Fikri is unique and different from other schools. MI Darul Fikri is a school that implements a class of homogeneous gender learning and there is a special class with the pattern of study class heterogeneous gender. It is noted that the Learning class grouping has a positive influence on students, i.e. the learning outcomes of learners inhomogeneous learning classes are better compared to heterogeneous learning classes. The purpose of this research is to reveal and analyze the influence of management of homogeneous learning classes on the concentration of students at MI Darul Fikri Ponorogo. This research uses observation methods, polls, and documentation. The population in this study involved all students of class III, IV, and V MI Darul Fikri in the school year 2019/2020 consisting of 7 groups with a total of 139 students. The sampling technique in this study used Proportionate stratified random sampling which was obtained by a representative sample of 100 respondents. The results showed that the management of homogeneous learning class in MI Darul Fikri is good with a percentage of 70%. The concentration of learning students at the management of homogeneous learning classes in MI Darul Fikri is also good with a percentage of 70%, and there is a positive and significant influence of management of the class of homogeneous learning to the learning concentration of students at MI Darul Fikri Ponorogo namely 78.3%